Fine Motor Skill Development Through Clamping Activities in Early Childhood: Pengembangan Keterampilan Motorik Halus Melalui Aktivitas Menjepit pada Anak Usia Dini - ALIVIA PUTRI; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Fine motor skills constitute a fundamental aspect of early childhood development, particularly in supporting children’s readiness for daily learning activities and future educational stages. Specific Background In PG&RA Baitul Muttaqin Sidoarjo, several children aged 3–4 years showed limited fine motor coordination, especially in grasping and manipulating small objects, indicating the need for structured classroom-based stimulation. Knowledge Gap Although fine motor activities are widely discussed, limited classroom action research documents step-by-step learning cycles that focus on clamping activities as a targeted motor skill exercise for children aged 3–4 years. Aims This study aims to describe the process and outcomes of implementing clamping activities to develop fine motor skills in early childhood learners. Results The findings indicate a progressive rise in fine motor skill achievement across learning stages, from the pre-cycle phase to Cycle I and Cycle II, as reflected in children’s improved grasping ability, object transfer skills, and hand–eye coordination, with overall achievement surpassing the predetermined success criteria in the final cycle. Novelty This study offers a detailed classroom action research depiction of clamping-based activities as a structured learning practice for fine motor skill development in early childhood settings. Implications The results provide practical guidance for early childhood educators in designing simple, engaging classroom activities that systematically support fine motor skill development. Highlights: Structured Learning Cycles Showed Consistent Progress in Children’s Small Muscle Coordination. Hands-on Tasks Supported Better Control in Grasping and Transferring Small Objects. Classroom-Based Activities Aligned With Developmental Indicators for Children Aged 3–4 Years. Keywords: Fine Motor Skills, Clamping Activities, Early Childhood Education, Classroom Action Research, Motor Development